Deep brain stimulation of the entopeduncular nucleus in rats prevents apomorphine-induced deficient sensorimotor gating - Posch, Dominic Konstantin; Schwabe, Kerstin; Krauss, Joachim K.; Lütjens, Götz (Behavioural brain research, 2012)
Pharmacologically induced stereotypies and deficient sensorimotor gating, measured as prepulse inhibition (PPI) of the acoustic startle response (ASR), are used as endophenotypes for certain symptoms common to neuropsychiatric disorders, such as schizophrenia and Tourette's syndrome (TS) among others. We here investigated whether high frequency deep brain stimulation (DBS) of the rat's entopeduncular nucleus (EPN), the equivalent to the human globus pallidus internus (GPi), would improve PPI-deficits and stereotypies induced by the dopamine receptor agonist apomorphine. Electrodes were stereotactically implanted bilaterally in the EPN of 13 Sprague-Dawley rats. After one week of recovery the rats were stimulated with an amplitude 20% below their individual threshold for side effects (130Hz, 80μs pulse width) or sham-stimulated for epochs of five days. At the end of each epoch the effect of ongoing stimulation or sham-stimulation on apomorphine-induced stereotypies (vehicle and 0.5mg/kg) and deficient PPI (vehicle and 1.0mg/kg) were tested. In nine rats, in which the full protocol could be applied and in which the electrode position was histologically confirmed in the target, EPN DBS did not affect baseline PPI but counteracted the apomorphine-induced PPI-deficit, while apomorphine-induced stereotypies were not affected by DBS. This work indicates an important role of the EPN in the modulation of apomorphine-induced deficient prepulse inhibition. This model may be useful to further investigate the pathophysiological of deficient sensorimotor gating and mechanisms of action of DBS in certain neuropsychiatric disorders.